Analysis of Potency and Strategy Identification of Wuluhan Subdistrict as A Super Priority Destination Area in Jember Regency - Prananta, Rebecha; Lokaprasidha, Pramesi; Nugroho, Margaretta Andini; Hutama, Pandu Satriya; Oktawirani, Panca (JSEP (Journal of Social and Agricultural Economics), 2024)
The potential of Wuluhan sub-district attracts the government to make a super priority area. This research with a cooperative tourism planning perspective will later present a normative model of tourism planning in Wuluhan area which requires integrative collaboration between government institutions and various stakeholders, both at the autonomous level and the public also private sectors. The analysis method in this research uses the PRA (Participatory Rural Appraisal) method, the strength, weakness, opportunity, and threat (SWOT) matrix analysis method and the quantitave strategy planning matrix (QSPM) method. The attractions in the four villages are agrotourism attractions, river tubing tourism, sports tourism, and recreational tourism. Accessibility to the four villages still needs development in terms of directional signage and improving road conditions. The amenities available in each village are still minimal and need improvement to support priority destinations. Ancillary services in each village already have tourism awareness group (pokdarwis), but there is still a need to improve human resources and governance. Based on the SWOT analysis, it was found: S-O strategy, W-O strategy, S-T strategy and W-T strategy to support super priority tourist areas.